2022
DOI: 10.3390/biomedicines10071742
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical and Morphological AFM Mapping of Normal Tissues and Tumors on Live Brain Slices Using Specially Designed Embedding Matrix and Laser-Shaped Cantilevers

Abstract: Cell and tissue nanomechanics has been intriguingly introduced into biomedical research, not only complementing traditional immunophenotyping and molecular analysis, but also bringing unexpected new insights for clinical diagnostics and bioengineering. However, despite the progress in the study of individual cells in culture by atomic force microscopy (AFM), its application for mapping live tissues has a number of technical limitations. Here, we elaborate a new technique to study live slices of normal brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…A number of pertinent studies have demonstrated that Young’s modulus can reflect the hardness of malignant cells or tissues, which are softer than normal tissue or cells. As a result, Young’s modulus is also thought to be an indication of changed cancerous tissue ( 40 ). The Young’s modulus of the tumor tissue in clear cell renal cell carcinomas was much lower than that of normal tissue, and the tumor tissue was significantly less fibrotic ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of pertinent studies have demonstrated that Young’s modulus can reflect the hardness of malignant cells or tissues, which are softer than normal tissue or cells. As a result, Young’s modulus is also thought to be an indication of changed cancerous tissue ( 40 ). The Young’s modulus of the tumor tissue in clear cell renal cell carcinomas was much lower than that of normal tissue, and the tumor tissue was significantly less fibrotic ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed AFM embedding matrix and laser-shaped cantilever enable nanomechanical and morphological mapping of live brain sections, differentiating between normal and tumor tissue. Biopsy preparation and AFM detection require a mere 55 min and can be conveniently combined with critical cell tracer analysis or immunostaining, showcasing its potential for biomedical research and clinical diagnosis (Farniev et al, 2022).…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…In a comparison of tissue sectioning techniques, vibratomed sections of living tissues have been shown to allow for the nanomechanical measurement of cells in tissues, while cryotomed sections inhibited the measurement of viable cells [83]. With an appropriate embedding matrix and modified AFM probes, measurement of the morphology and nanomechanics of live brain tissues has been demonstrated [84].…”
Section: Mechanoelastic Properties Of Neurons and Tissuesmentioning
confidence: 99%